EFFECTIVENESS OF 48 WEEKS INTERFERON ALFA 2-B IN COMBINATION WITH RIBAVIRIN AS INITIAL TREATMENT OF CHRONIC HEPATITIS - Khokhar, Nasir (Journal of Ayub Medical College Abbottabad, 2002)
Background: Chronic hepatitis C is a common problem worldwide and is becoming an increasingly common problem in Pakistan. This study was done to evaluate effectiveness and safety of 48 weeks combination treatment with Interferon and Ribavirin as initial therapy of chronic hepatitis C patients. Methods: One hundred consecutive patients were prospectively evaluated and treated with combination of Interferon Alfa 2-b three million units subcutaneously three injection weekly and Ribavirin 800-1200 mg orally daily for 48 weeks and followed for another 6 months. End of the treatment, sustained viral response and side effects were noted. Results: Of one hundred patients, 98 completed the treatment. There were 55 males and 43 females. Ages range from 21-60 years, mostly being 31-55 years. Over 83% responded at the end of treatment and four relapsed. Out of treated, 72.7% males and 88.3% females had sustained viral response with a total combined sustained viral response rate of 79.5%. Patients with cirrhosis had 85.7 sustained viral response. Four percent patients took longer than three months to show HCV RNA negativity. Side effects were usual and tolerable and only 2% discontinued the treatment. Non-responders were mostly males above age 50. Conclusion: Forty-eight weeks combination treatment with Interferon alfa 2-b and Ribavirin has given 79.5% sustained viral response in our patients and treatment was well tolerated. Key Words: Chronic hepatitis C, Interferon, Ribavirin